Anticonvulsant effects of bretazenil (Ro 16-6028) during ontogenesis - Kubová, H; Rathouská, J; Mares, P (Epilepsia, 1993)
Anticonvulsant action of a new benzodiazepine, bretazenil (Ro 16-6028), was studied in 240 rats in five age groups: age 7, 12, 18, 25 and 90 days. Motor seizures induced by metrazol (pentamethylenetetrazol, PTZ, 100 mg/kg subcutaneously (s.c.) except for 18-day-old rats which received a dose of 90 mg/kg) served as a model. Animals were pretreated with Ro 16-6028 in doses of 0.001-0.1 mg/kg intraperitoneally (i.p.) 10 min before metrazol. Both types of metrazol-induced seizures, minimal (mMS, predominantly clonic with preserved righting ability) and major (MMS, generalized tonic-clonic), were suppressed by Ro 16-6028 in a dose-dependent manner. Major seizures were always more sensitive to Ro 16-6028 than were minimal seizures. The youngest rats exhibited maximal effects of Ro 16-6028 against major seizures. On the other hand, this drug increased the incidence of minimal seizures in 7- and 12-day-old rats, i.e., in age groups in which this type of seizure is rare under control conditions.
Keywords: Pentylenetetrazole; Epilepsy; epilepsie; Humans; Kindling, Neurologic; dítě; Child; benzodiazepinony; Dose-Response Relationship, Drug; Female; dospělí; injekce intraperitoneální; krysa rodu Rattus; lidé; zvířata; pentylentetrazol; Injections, Intraperitoneal; Adult; Benzodiazepinones; receptory GABA; Receptors, GABA; ženské pohlaví; Male; kindling; Rats; vztah mezi dávkou a účinkem léčiva; Animals; mužské pohlaví